Antibody-based candidate therapeutics against HIV-1: implications for virus eradication and vaccine design. (June 2013) - Chen, Weizao; Ying, Tianlei; Dimitrov, Dimiter S
<x xml:space="preserve">Abstract</x> Introduction: The currently available anti-HIV-1 drugs can control the infection but do not eradicate the virus. Their long-term use can lead to side effects and resistance to therapy. Therefore, eradication of the virus has been a major goal of research. Biological therapeutics including broadly neutralizing monoclonal antibodies (bnAbs) are promising tools to reach this goal. They could also help design novel vaccine immunogens potentially capable of eliciting bnAbs targeting the HIV-1 envelope glycoproteins (Envs). Areas covered: We review HIV-1 bnAbs and their potential as candidate prophylactics and therapeutics used individually, in combination, or as bispecific fusion proteins. We also discuss their potential use in the 'activation-elimination' approach for HIV-1 eradication in infected patients receiving antiretroviral treatment as well as current vaccine design efforts based on understanding of interactions of candidate vaccine immunogens with matured bnAbs and their putative germline predecessors, and related antibody maturation pathways. Expert opinion: Exploration of HIV-1 bnAbs has provided and will continue to provide useful knowledge that helps develop novel types of biotherapeutics and vaccines. It is possible that bnAb-based candidate therapeutics could help eradicate HIV-1. Development of vaccine immunogens capable of eliciting potent bnAbs in humans remains a fundamental challenge.